PENGHORMATAN DAN DUKACITA: ANALISIS PASTORAL KONSELING TERHADAP TRADISI PEMASANGAN LILIN PADA TEMPAT KECELAKAAN DI MANADO - Yohan Brek; Fani Sapoh (Institut Agama Kristen Negeri Manado, 2024)
This article explores the role of pastoral counseling in supporting the candle-lighting tradition at accident sites in Manado. With the rising traffic accident rates in North Sulawesi, the tradition of lighting candles at accident locations has become an important means for the community to express grief, respect, and solidarity with the victims and their families. Through a qualitative approach, this study employs a case study design to understand the meaning and processes behind the candle-lighting tradition and how pastoral counseling can assist individuals and communities in the grieving process. The research findings indicate that the candle-lighting tradition in Manado not only serves as a tribute to the deceased but also strengthens community bonds and raises awareness about traffic safety. Pastoral counseling plays a crucial role by offering holistic support, both emotional and spiritual, helping families find meaning in their loss and gain strength through faith. Through case studies and individual narratives, this article demonstrates the effectiveness of pastoral counseling in supporting the grieving process. The main challenge lies in understanding and respecting cultural values and local traditions, requiring pastoral counselors to be sensitive to local cultural practices. This research contributes to the literature by filling the gap regarding the integration of local traditions with pastoral counseling practices. The findings emphasize the importance of education and training for pastoral counselors to understand cultural values and local traditions to provide more effective support. Thus, this article offers new insights into how pastoral counseling can be effectively applied to support the grieving process within the context of local traditions.